Multi-layer composite reinforced material and application of preparation method thereof in prevention and treatment of reflection cracks of widened roadbed
By using multi-layer composite reinforcement materials, including stress absorption layer, adhesive layer and asphalt concrete layer during the roadbed widening process, and using specific fibers and modifiers, the limitations of reflective crack prevention and control in the prior art are solved, and more efficient stress absorption and dispersion are achieved, and the stability and crack resistance of the road are significantly improved.
Patent Information
- Application Number
- CN202411847142.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The prior art has limitations in preventing and controlling reflective cracks during roadbed widening. For example, the material selection and laying process of stress absorption method affect the effect, the crack prevention effect of glass fiber grating reinforcement method decreases when facing shear-type reflective cracks, and the crack relief layer method needs to consider material properties and construction conditions.
Multi-layer composite reinforcement materials are used, including stress absorption layer, adhesive layer and asphalt concrete layer. By adding PVA fibers and modified carbon fibers to the stress absorption layer, nanosilicon dioxide modified carbon fibers of different particle sizes are used, and asphalt with high needle penetration and high ductility and specific modifiers are selected to form composite materials with excellent crack resistance.
It effectively alleviates the stress concentration caused by roadbed deformation, reduces the generation of reflective cracks, significantly improves the overall stability and crack resistance of the road structure, and is suitable for widening the reflection crack prevention and control of roadbeds.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of composite pavement structures, and in particular relates to an application of a multi-layer composite reinforcement material and a preparation method thereof in the prevention and treatment of reflective cracks in a widened roadbed. Background Art
[0002] With the continuous growth of transportation demand, highway widening projects have become one of the important tasks of current road construction. In the process of highway widening, especially in the widening of roadbed, reflective cracks are often encountered. Reflective cracks refer to cracks in the road surface of the widened part due to the combined effects of uneven settlement of the new and old roadbeds, temperature changes, humidity changes and vehicle loads when widening on the basis of the original road. These cracks will gradually develop upwards, affecting the performance and service life of the road.
[0003] At present, common roadbed widening methods include single-side splicing and double-side widening. Although single-side splicing can reduce the construction space occupied, in actual operation, since the widened side needs to be paved accordingly, it is difficult to ensure the balance of the overall pavement thickness and the overall smoothness of the pavement. The double-side widening method does not require adjustment of the pavement arch slope, and can make full use of the original pavement. The construction is relatively simple and the cost is low. However, no matter which method is used, the problem of reflective cracks is still difficult to avoid.
[0004] In order to prevent and control reflective cracks, existing technical means mainly include stress absorption method, glass fiber grid reinforcement method, crack mitigation layer method, etc. The stress absorption method eliminates stress concentration by setting an isolation layer between the overlay layer and the original pavement, such as geotextile, oil felt, etc., to absorb stress. The glass fiber grid reinforcement method is to lay glass fiber grid in the overlay layer to enhance the overall tensile strength of the asphalt mixture and improve the stress distribution of the pavement structure, thereby resisting and delaying the occurrence of reflective cracks. The crack mitigation layer method uses materials such as large-particle permeable asphalt concrete to form a crack mitigation layer to mitigate the expansion of reflective cracks.
[0005] However, existing technical means still have certain limitations in preventing and controlling reflective cracks. For example, the selection of isolation layer materials and laying process in the stress absorption method will affect its effect; the anti-crack effect of the glass fiber grid reinforcement method will be reduced when facing shear-type reflective cracks; the crack mitigation layer method needs to take into account factors such as material performance, construction conditions and long-term performance.
[0006] Therefore, developing a new type of multi-layer composite reinforcement material and a preparation method thereof for preventing and treating reflective cracks in widened roadbeds has important practical significance and application value. Summary of the invention
[0007] The purpose of the present invention is to provide a multi-layer composite reinforced material and a preparation method thereof, wherein the multi-layer composite reinforced material has excellent stress absorption, dispersion and bonding effects, can effectively alleviate the stress concentration caused by roadbed deformation, reduce the occurrence of reflective cracks, and significantly improve the overall stability and crack resistance of the road structure.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] A multi-layer composite reinforcement material, which comprises a stress absorption layer, a bonding layer and an asphalt concrete layer from bottom to top.
[0010] The raw materials for preparing the stress absorbing layer include gelling material, river sand, fiber, water reducing agent and water.
[0011] Preferably, the cementitious material includes cement, silica fume and fly ash.
[0012] Preferably, the mass ratio of the cement, silica fume and fly ash is (2.5-3.5):1:(5-7); further preferably, it is 3:1:6.
[0013] Preferably, the cement is ordinary Portland cement with a P·O 42.5, an initial setting time of 220-230 min, a final setting time of 280-290 min, and a specific surface area of ≥350 m 2 / kg, sulfur trioxide content ≤2.2%.
[0014] In some preferred embodiments, the cement is purchased from Jidong Heidelberg (Jingyang) Cement Co., Ltd.
[0015] Preferably, the silica content in the silica ash is ≥92%, the loss on ignition is ≤2%, and the 7d activity index is ≥102%.
[0016] In some preferred embodiments, the silica fume is purchased from Gansu Sanyuan Silicon Materials Co., Ltd.
[0017] Preferably, the fly ash is first-grade fly ash, with fineness (residue on 45 mm square sieve) ≤ 9%, water requirement ratio ≤ 93%, and loss on ignition ≤ 2.7%.
[0018] In some preferred embodiments, the fly ash is purchased from Jinchang Zhongtianyuan Industry and Trade Co., Ltd.
[0019] Preferably, the particle size of the river sand is ≤0.2 mm, and each index meets the relevant requirements of GB / T 14684-2022 "Construction Sand", and the river sand is obtained by passing commercially purchased river sand through a 0.5 mm sieve.
[0020] In some preferred embodiments, the river sand is purchased from the Manba River Sand Factory in Lintao County.
[0021] Preferably, the fibers include PVA fibers and modified carbon fibers.
[0022] Preferably, the volume ratio of the PVA fiber to the modified carbon fiber is (1-3):1; further preferably, it is 2:1.
[0023] Preferably, the PVA fiber has a diameter of 38-40 μm, a length of 12-13 μm, a tensile strength of 1550-1650 MPa, and an elongation at break of 6%-7%.
[0024] In some preferred embodiments, the PVA fiber is purchased from Kuraray of Japan.
[0025] By adding PVA fiber and carbon fiber to the stress absorption layer, the strength and toughness of the stress absorption layer can be significantly improved, thereby improving the overall mechanical properties and durability of the multilayer composite reinforced material. This may be because there is a synergistic effect between PVA fiber and carbon fiber. On the one hand, PVA fiber has excellent corrosion resistance, weather resistance and good interfacial adhesion with the matrix material, which can enhance the overall strength of the material. Carbon fiber can effectively improve the tensile strength and stiffness of the material. When the two are used in combination, they can form a complementary effect and significantly improve the overall strength of the stress absorption layer. On the other hand, the flexibility and strain capacity of PVA fiber help the material to better absorb and disperse stress when subjected to external force, preventing the generation and expansion of cracks. The rigidity of carbon fiber can increase the material's deformation resistance, so that it can still maintain the integrity of the structure when subjected to large external forces. The combination of the two can significantly improve the toughness and crack resistance of the stress absorption layer. However, carbon fiber is brittle, prone to cracking, and has poor thermal stability, which may affect the overall mechanical properties and durability of the stress absorption layer.
[0026] The method for preparing the modified carbon fiber comprises the following steps:
[0027] S1. Modification of nano-silica: After nano-silica is dispersed evenly in an ethanol aqueous solution, a silane coupling agent is added, and the mixture is stirred at 60-70° C. for 4-6 hours, filtered, washed with deionized water for 2-3 times, filtered under reduced pressure, and dried in vacuum to obtain modified nano-silica;
[0028] S2. Surface treatment and activation of carbon fiber: put the carbon fiber into a beaker containing acetone, use an ultrasonic cleaner to clean it 2-3 times, each time for 20-30 minutes, dry it, use oxygen plasma to treat the surface of the carbon fiber at a power of 45-55W, and the treatment time is 3-5 minutes to obtain activated carbon fiber;
[0029] S3. Ultrasonic dispersion of modified nano-silica in toluene, immersion in activated carbon fiber, reaction at 80-100° C. for 3-5 hours, filtration, washing with ethanol for 3-5 times, and vacuum drying at 100° C. to obtain modified carbon fiber.
[0030] Preferably, the nano-silicon dioxide includes a first nano-silicon dioxide, a second nano-silicon dioxide, and a third nano-silicon dioxide.
[0031] Preferably, the mass ratio of the first nano-silicon dioxide, the second nano-silicon dioxide, and the third nano-silicon dioxide is (0.5-2):(0.5-2):1; more preferably, it is 1:1:1.
[0032] Preferably, the average particle size of the first nano-silicon dioxide is 15 nm and the specific surface area is 250 m 2 / g.
[0033] Preferably, the average particle size of the second nano-silicon dioxide is 30 nm and the specific surface area is 200 m 2 / g.
[0034] Preferably, the average particle size of the third nano-silicon dioxide is 60 nm, and the specific surface area is 150 to 200 m 2 / g.
[0035] In some preferred embodiments, the nano-silicon dioxide is purchased from Beijing Dekedaojin Technology Co., Ltd.
[0036] Preferably, the volume concentration of ethanol in the ethanol aqueous solution is 60% to 70%.
[0037] Preferably, the mass ratio of the nano-silicon dioxide to the ethanol aqueous solution is 1:(20-30).
[0038] Preferably, the silane coupling agent includes hexamethyldisilazane and γ-mercaptopropyltrimethoxysilane.
[0039] Preferably, the mass ratio of hexamethyldisilazane to γ-mercaptopropyltrimethoxysilane is (1-3):1; more preferably, it is 2:1.
[0040] Preferably, the added amount of the silane coupling agent is 10% to 20% of the mass of the nano-silicon dioxide.
[0041] Preferably, the carbon fiber has a diameter of 6-8 μm and a density of 1.70-1.80 g / cm 3 , elongation ≥1.5%, tensile strength ≥3GPa.
[0042] In some preferred embodiments, the carbon fiber is purchased from Jilin Jiyan High-Tech Fiber Co., Ltd.
[0043] Preferably, the mass ratio of the carbon fiber to acetone is 1:(20-40).
[0044] Preferably, the mass ratio of the modified nano-silica to toluene is 1:(80-100).
[0045] Preferably, the ultrasonic conditions are: power 100-200W, time 30-50min.
[0046] Preferably, the mass ratio of the modified nano-silica to the activated carbon fiber is 1:(2-4); further preferably, it is 1:3.
[0047] Using nano-silica of different particle sizes to modify carbon fiber can significantly improve the defects of carbon fiber such as large brittleness, easy cracking, and poor high temperature resistance, thereby improving the relevant properties of stress absorption layer and multi-layer composite reinforcement materials. This may be because on the one hand, the surface of nano-silica has abundant active groups such as hydroxyl groups, which can react chemically or physically adsorb with the functional groups on the surface of carbon fiber, thereby enhancing the interfacial bonding force between carbon fiber and matrix material, helping to reduce the generation and expansion of cracks and improve the overall strength of the material. On the other hand, the addition of nano-silica can fill the gaps between carbon fibers to form a more compact structure. At the same time, nano-silica of different particle sizes can form a multi-level dispersed structure, which helps to disperse and absorb stress, thereby improving the toughness of the material, helping to reduce the brittle fracture of carbon fiber during stress, and extending the service life of the material. In addition, nano-silica has excellent thermal stability and can maintain structural stability at high temperatures. By introducing it into carbon fiber, the thermal stability of carbon fiber and its composite materials can be improved, and the performance degradation under high temperature environment can be reduced, which is more suitable for road construction in extreme weather.
[0048] Preferably, the water reducer is a polycarboxylate water reducer with a water reduction rate of ≥30%, a net slurry fluidity of ≥210 mm, and a bulk density of 400-700 kg / m 3 .
[0049] In some preferred embodiments, the water reducing agent is purchased from Nanjing Xinyi Synthetic Technology Co., Ltd.
[0050] Preferably, the added amount of the water reducing agent is 1%-2% of the total mass of cement and fly ash.
[0051] Preferably, in the raw materials for preparing the stress absorbing layer, the water-to-binder ratio is 0.2-0.3, the sand-to-binder ratio is 0.3-0.4, and the fiber incorporation volume ratio is 1%-2.5%.
[0052] The method for preparing the stress absorption layer comprises the following steps:
[0053] A1. Add the cementitious material and river sand into the mixer and stir at 100-150r / min for 3-5min;
[0054] A2. Mix water and water reducer, pour into mixer, stir at 100-150r / min for 3-5min, then stir at 200-300r / min for 3-5min, sprinkle into fiber and stir at 200-300r / min for 5-10min.
[0055] The raw materials for preparing the bonding layer include, by weight, 95-100 parts of a first matrix asphalt, 2-5 parts of rubber, 1-5 parts of a tackifying resin, and 0.5-1 parts of a first emulsifier.
[0056] Preferably, the first matrix asphalt has a softening point of 45-50°C, a needle penetration of 80-85 (0.1 mm) at 25°C, an elongation of 65-70 cm at 10°C, and a dynamic viscosity of 165-180 Pa·s at 60°C.
[0057] In some preferred embodiments, the first matrix asphalt is purchased from SK, No. 90 asphalt from South Korea.
[0058] Preferably, the rubber comprises SBR.
[0059] Preferably, the SBR has a styrene content of 22%-25%, an elongation at break of ≥34%, and a volatility of 0.6%.
[0060] In some preferred embodiments, the SBR is purchased from Jilin Kunlun, 1502.
[0061] Preferably, the tackifying resin includes one or more of petroleum resin, rosin resin, and terpene resin; more preferably, it is petroleum resin.
[0062] Preferably, the petroleum resin is C9 hydrogenated petroleum resin, with a softening point of 105-115° C. and an acid value of ≤1 mgKOH / g.
[0063] In some preferred embodiments, the petroleum resin is purchased from Puyang Hengtai Petrochemical Co., Ltd.
[0064] Preferably, the first matrix asphalt emulsifier is a diquaternary ammonium salt type medium-split cationic asphalt emulsifier with an active matter content of 48%-52% and a pH of 5-7.
[0065] In some preferred embodiments, the first base asphalt emulsifier is purchased from Shanghai Shijian Industrial Co., Ltd.
[0066] Selecting SK90 asphalt with large penetration and high ductility as the raw material of the bonding layer can improve the flexibility and plasticity of the bonding layer, facilitate its close combination with the upper and lower pavement layers, and adapt to the deformation and displacement of the pavement. Selecting specific SBR and C9 hydrogenated petroleum resin to modify the asphalt not only significantly improves the viscosity of the bonding layer, but also improves its temperature stability. This may be because on the one hand, SBR molecules dispersed in the asphalt will not only produce physical entanglement, but also absorb the oil in the asphalt, so that the distance between asphaltene and SBR is reduced, the volume of SBR absorbing oil increases, and the resistance during flow increases, thereby increasing the viscosity of the asphalt. In addition, because the modulus of SBR rubber particles is different from that of the asphalt matrix, a high degree of stress concentration can be generated at low temperatures, inducing a large number of silver streaks and shear bands, consuming a lot of energy, and improving the impact strength and plasticity of the bonding layer. Larger SBR rubber particles can also prevent the growth and breakage of single silver streaks, avoiding their rapid development into destructive cracks, thereby improving the low-temperature flexibility of asphalt. On the other hand, C9 hydrogenated petroleum resin has excellent miscibility and thermal stability. When added to asphalt, it can cross-link with asphalt to form a spatial network structure that interpenetrates each other, thereby increasing the viscosity of asphalt. In the bonding layer, the first matrix asphalt, as the basis, forms a tight structure with SBR through physical adsorption, diffusion and possible chemical bonding, and at the same time, it uses polar interactions and molecular chain entanglement with C9 hydrogenated petroleum resin to enhance adhesion and cohesion. The diquaternary ammonium salt type medium crack cationic asphalt emulsifier ensures the uniform dispersion and stability of asphalt through emulsification dispersion and interfacial film formation, while promoting interfacial bonding with other raw materials. The combination of SBR and C9 hydrogenated petroleum resin not only enhances adhesion, but also improves elastic modulus and processing performance, while the synergy of C9 hydrogenated petroleum resin and emulsifier further stabilizes the emulsification system, optimizes the microstructure, and enhances interfacial bonding. These synergistic effects jointly improve the adhesion, durability, crack resistance and peeling resistance of the bonding layer, thereby enhancing the overall performance and service life of the multi-layer composite reinforcement material.
[0067] The preparation method of the bonding layer comprises the following steps: heating the first matrix asphalt to 155-165°C, adding rubber, tackifying resin and the first emulsifier, stirring for 1-2 hours, heating to 170-180°C, shearing with a colloid mill at a rotation speed of 3000-4000 r / min for 1-2 hours, heating to 180-190°C, shearing with a colloid mill at a rotation speed of 3000-4000 r / min for 1-2 hours, stopping shearing, stirring and maturing for 30-60 minutes, and cooling to obtain the product.
[0068] The raw materials for preparing the asphalt concrete layer include modified asphalt, curing agent and mineral material.
[0069] The raw materials for preparing the modified asphalt include, by weight, 95-105 parts of second matrix asphalt, 3-8 parts of thermoplastic elastomer, 8-15 parts of epoxy resin, 0.5-1 part of second matrix asphalt emulsifier, and 1-2.5 parts of epoxy resin emulsifier.
[0070] Preferably, the second matrix asphalt has a softening point of 45-50°C, a needle penetration of 66-70 (0.1 mm) at 25°C, an elongation of 18-22 cm at 10°C, and a dynamic viscosity of 210-220 Pa·s at 60°C.
[0071] In some preferred embodiments, the second base asphalt is purchased from Maoming Branch of Sinopec Co., Ltd., No. 70 Road Petroleum Asphalt (1-4) (Grade A).
[0072] Preferably, the thermoplastic elastomer is SBS, with a melt flow rate of 2-5 g / 10 min at 190° C., a volatility of ≤0.8%, and a total styrene content of 38%-42%.
[0073] In some preferred embodiments, the SBS is purchased from Dushanzi Petrochemical, T171 E.
[0074] Preferably, the epoxy resin is bisphenol A epoxy resin, with an epoxy equivalent of 230-290 mol / 100g and a softening point of 21-27°C.
[0075] In some preferred embodiments, the epoxy resin is purchased from Laizhou Baichen Insulation Material Co., Ltd., resin E-42.
[0076] The use of specific SBS and bisphenol A epoxy resin to modify No. 70 asphalt can significantly improve the crack resistance, overall stability and construction performance of the asphalt concrete layer, providing a more reliable material guarantee for the prevention and control of reflective cracks in widened roadbeds. This may be because the addition of SBS significantly enhances the elastic recovery and low-temperature crack resistance of asphalt, and absorbs the light oil in the asphalt through its soft segment and fully swells to form a spatial network system, effectively reducing cracks caused by temperature changes. At the same time, bisphenol A epoxy resin cross-links with the functional groups on the asphalt molecules to form a three-dimensional interpenetrating network structure, which greatly improves the high-temperature stability and adhesion of the asphalt, and fundamentally changes the thermoplasticity of ordinary asphalt. The synergistic effect of the two not only complements each other, improves the elasticity, strength and stability of the modified asphalt, but also optimizes the cross-linking reaction process, making the reaction more sufficient and uniform.
[0077] Preferably, the second matrix asphalt emulsifier is a cationic amide slow-cracking and fast-setting emulsifier with an active matter content of 89%-91% and a pH value of 6-7.
[0078] In some preferred embodiments, the second base asphalt emulsifier is purchased from Shandong Boxing County Haolong Chemical Co., Ltd.
[0079] Preferably, the epoxy resin emulsifier is a non-ionic water-dispersible emulsion with a solid content of 38%-42%, a viscosity of 900-1200 mP·s at 25° C., and a specific gravity of 1.01-1.08.
[0080] In some preferred embodiments, the epoxy resin emulsifier is purchased from Dongguan Guangtong Chemical Products Co., Ltd.
[0081] The preparation method of the modified asphalt comprises the following steps:
[0082] B1. Preparation of epoxy resin emulsion: epoxy resin, epoxy resin emulsifier and water are mixed, and sheared at a speed of 3000-4000 r / min for 30-50 min to obtain epoxy resin emulsion;
[0083] B2. Preparation of modified second matrix asphalt: dissolving the second matrix asphalt emulsifier in 60° C. water to obtain a second matrix asphalt emulsifier solution; raising the temperature of the second matrix asphalt to 175-180° C., adding the second matrix asphalt emulsifier solution, shearing the mixture with a colloid mill at a speed of 3000-4000 r / min for 20-40 min, adding a thermoplastic elastomer, continuing to shear the mixture with a colloid mill at a speed of 3000-4000 r / min for 40-60 min, and cooling the mixture to obtain the modified second matrix asphalt;
[0084] B3. Mix the epoxy resin emulsion and the modified second matrix asphalt, and shear them at a speed of 300-500r / min for 5-10min.
[0085] Preferably, the amount of water added in step B1 is consistent with the mass of the epoxy resin.
[0086] Preferably, the amount of water added in step B2 is 90-110 times the mass of the second matrix asphalt emulsifier.
[0087] Preferably, the solid content of the curing agent is 43%-47%, the viscosity at 25° C. is 7700-9600 mP·s, and the amine hydrogen equivalent is 220-280.
[0088] In some preferred embodiments, the curing agent is purchased from Dongguan Guangtong Chemical Products Co., Ltd.
[0089] The mineral materials include coarse aggregate, fine aggregate and filler. The specific proportions and properties refer to the article "Study on the Flexural Properties and Triaxial Static and Dynamic Characteristics of SBS Modified Asphalt Concrete for Anti-seepage Layer in Cold Regions" published by Ning Fengwei et al.
[0090] Preferably, the mass ratio of the modified asphalt to the curing agent is (2-3):1; further preferably, it is 5:2.
[0091] Preferably, the mass of the modified asphalt is 8%-15% of the mass of the mineral material, and the gradation index is 0.43.
[0092] The preparation method of the asphalt concrete layer comprises the following steps: mixing the modified asphalt and the curing agent, shearing for 5-10 minutes under the conditions of 150-160° C. and 800-1200 r / min, adding mineral material, and stirring for 20-40 minutes to obtain the asphalt concrete layer.
[0093] The second aspect of the present invention provides a method for preparing the multi-layer composite reinforced material, comprising the steps of: simultaneously spreading a stress absorption layer, an adhesive layer, and an asphalt concrete layer, compacting them, and curing them at room temperature for 28 days to obtain the material.
[0094] Preferably, the stress absorption layer has a thickness of 6-10 mm.
[0095] Preferably, the amount of the adhesive layer sprayed is 1-1.2 kg / m 2
[0096] Preferably, the thickness of the asphalt concrete layer is 4-8 mm.
[0097] In some preferred embodiments, the stress absorbing layer and the asphalt concrete layer are heated to 180-190°C before spreading, and the bonding layer temperature is 160-170°C.
[0098] The third aspect of the present invention provides the application of the multi-layer composite reinforcement material in the prevention and treatment of reflective cracks in widened roadbed, and the specific application method is:
[0099] C1. After excavating the cracks and cleaning the excavated area, fill the filling materials into the excavated cracks and compact the filled road surface with a 10-ton roller;
[0100] C2. Pour the caulking material into the cracks of the pavement, control the temperature of the caulking material between 160-180℃, and after the cracks of the pavement are fully filled, simultaneously spread the stress absorption layer, bonding layer and asphalt concrete layer, compact them and maintain for 28 days.
[0101] Preferably, the filling material is not specifically limited and can be gravel, concrete and other materials with a particle size of 10-30 mm.
[0102] The raw material and preparation method of the caulking material are consistent with the raw material and preparation method of the bonding layer.
[0103] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0104] 1. The present invention provides a multi-layer composite reinforcement material, which includes a stress absorption layer, an adhesive layer and an asphalt concrete layer from bottom to top. By selecting specific raw materials, each layer of material has a specific stress absorption and dispersion ability, and through a specific preparation process, these layered materials are tightly combined together to form a composite reinforcement material with excellent crack resistance. It has excellent stress absorption, dispersion and bonding effects, can effectively alleviate the stress concentration caused by roadbed deformation, reduce the generation of reflective cracks, and significantly improve the overall stability and crack resistance of the road structure. It is very suitable for the prevention and control of reflective cracks in widened roadbeds.
[0105] 2. The present invention can significantly improve the strength and toughness of the stress absorption layer by adding PVA fibers and carbon fibers to the stress absorption layer, thereby improving the overall mechanical properties and durability of the multilayer composite reinforced material.
[0106] 3. The present invention uses nano-silicon dioxide of different particle sizes to modify carbon fiber, which can significantly improve the defects of carbon fiber such as high brittleness, easy cracking, and poor high temperature resistance, thereby improving the relevant performance of the stress absorption layer and the multi-layer composite reinforcement material.
[0107] 4. The present invention selects SK90 asphalt with large needle penetration and high ductility as the raw material of the bonding layer, which can improve the flexibility and plasticity of the bonding layer, facilitate its close combination with the upper and lower road surfaces, and adapt to the deformation and displacement of the road surface.
[0108] 5. The present invention uses specific SBS and bisphenol A epoxy resin to modify No. 70 asphalt, which can significantly improve the crack resistance, overall stability and construction performance of the asphalt concrete layer, and provide a more reliable material guarantee for the prevention and control of reflective cracks in widened roadbeds. DETAILED DESCRIPTION
[0109] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0110] The raw materials used in the present invention are all commercially available, specifically:
[0111] The cement is ordinary Portland cement with a P·O 42.5, initial setting time of 220-230min, final setting time of 280-290min, and specific surface area ≥350m 2 / kg, sulfur trioxide content ≤2.2%, purchased from Jidong Heidelberg (Jingyang) Cement Co., Ltd.
[0112] The silica ash has a silicon dioxide content of ≥92%, a loss on ignition of ≤2%, and a 7d activity index of ≥102%, and was purchased from Gansu Sanyuan Silicon Materials Co., Ltd.
[0113] The fly ash is first-grade fly ash with fineness (residue on 45 mm square sieve) ≤9%, water requirement ratio ≤93%, and loss on ignition ≤2.7%, purchased from Jinchang Zhongtianyuan Industry and Trade Co., Ltd.
[0114] The particle size of river sand is ≤0.2mm, and all indicators meet the relevant requirements of GB / T 14684-2022 "Construction Sand". It is city-purchased river sand that passes through a 0.5mm sieve and is purchased from the Manba River Sand Factory in Lintao County.
[0115] The PVA fiber has a diameter of 38-40 μm, a length of 12-13 μm, a tensile strength of 1550-1650 MPa, and an elongation at break of 6%-7%, and is purchased from Kuraray, Japan.
[0116] The average particle size of the first nano-silicon dioxide is 15nm and the specific surface area is 250m 2 / g; the average particle size of the second nano-silicon dioxide is 30nm and the specific surface area is 200m 2 / g; the average particle size of the third nano-silicon dioxide is 60nm, and the specific surface area is 150-200m 2 / g; all purchased from Beijing Dekedao Gold Technology Co., Ltd.
[0117] The diameter of carbon fiber is 6-8μm and the density is 1.70-1.80g / cm 3 , elongation ≥ 1.5%, tensile strength ≥ 3 Gpa, purchased from Jilin Jiyan High-tech Fiber Co., Ltd.
[0118] The water reducer is polycarboxylate water reducer, with a water reduction rate of ≥30%, a net slurry fluidity of ≥210mm, and a bulk density of 400-700kg / m 3 , purchased from Nanjing Xinyi Synthetic Technology Co., Ltd.
[0119] The first matrix asphalt has a softening point of 45-50°C, a needle penetration of 80-85 (0.1 mm) at 25°C, an elongation of 65-70 cm at 10°C, and a dynamic viscosity of 165-180 Pa·s at 60°C. It is purchased from SK, South Korea, and is No. 90 asphalt.
[0120] The styrene content of SBR is 22%-25%, the elongation at break is ≥34%, and the volatility is 0.6%. It is purchased from Jilin Kunlun, 1502.
[0121] C9 hydrogenated petroleum resin, softening point of 105-115°C, acid value ≤1mgKOH / g, purchased from Puyang Hengtai Petrochemical Co., Ltd.
[0122] The first matrix asphalt emulsifier is a diquaternary ammonium salt type medium-crack cationic asphalt emulsifier with an active matter content of 48%-52% and a pH of 5-7, purchased from Shanghai Shijian Industrial Co., Ltd.
[0123] The second matrix asphalt has a softening point of 45-50°C, a needle penetration of 66-70 (0.1 mm) at 25°C, an elongation of 18-22 cm at 10°C, and a dynamic viscosity of 210-220 Pa·s at 60°C. It was purchased from Maoming Branch of Sinopec, No. 70 Road Petroleum Asphalt (1-4) (Grade A).
[0124] SBS has a melt flow rate of 2-5 g / 10 min at 190°C, volatility ≤0.8%, and a total styrene content of 38%-42%. It was purchased from Dushanzi Petrochemical, T171 E.
[0125] Bisphenol A type epoxy resin, epoxy equivalent of 230-290 mol / 100g, softening point of 21-27°C, purchased from Laizhou Baichen Insulation Material Co., Ltd., resin E-42.
[0126] The second matrix asphalt emulsifier is a cationic amide slow-cracking and fast-setting emulsifier with an active matter content of 89%-91% and a pH value of 6-7, which was purchased from Shandong Boxing County Haolong Chemical Co., Ltd.
[0127] The epoxy resin emulsifier is a non-ionic water-dispersible emulsion with a solid content of 38%-42%, a viscosity of 900-1200 mP·s at 25° C., and a specific gravity of 1.01-1.08, purchased from Dongguan Guangtong Chemical Products Co., Ltd.
[0128] The curing agent has a solid content of 43%-47%, a viscosity of 7700-9600 mP·s at 25° C., and an amine hydrogen equivalent of 220-280. It is purchased from Dongguan Guangtong Chemical Products Co., Ltd.
[0129] Example 1
[0130] This embodiment provides a multi-layer composite reinforcement material, which includes, from bottom to top, a stress absorption layer, an adhesive layer, and an asphalt concrete layer.
[0131] The raw materials for preparing the stress absorbing layer are cementitious material, river sand, fiber, water reducing agent and water.
[0132] The cementitious material is cement, silica fume and fly ash, and the mass ratio is 3:1:6.
[0133] The fibers are PVA fibers and modified carbon fibers, with a volume ratio of 2:1.
[0134] The preparation method of the modified carbon fiber comprises the following steps:
[0135] S1. Modification of nano-silica: After nano-silica is dispersed evenly in an ethanol aqueous solution, a silane coupling agent is added, and the mixture is stirred at 65° C. for 5 h, filtered, washed with deionized water for 3 times, filtered under reduced pressure, and dried in vacuum to obtain modified nano-silica;
[0136] S2. Surface treatment and activation of carbon fiber: put the carbon fiber into a beaker containing acetone, clean it 3 times with an ultrasonic cleaner, each time for 25 minutes, dry it, and treat the surface of the carbon fiber with oxygen plasma at a power of 50 W for 4 minutes to obtain activated carbon fiber;
[0137] S3. Ultrasonic dispersion of modified nano-silica in toluene, immersion in activated carbon fiber, reaction at 90°C for 4 hours, filtration, washing with ethanol 4 times, and vacuum drying at 100°C to obtain modified carbon fiber.
[0138] The nano silicon dioxide includes first nano silicon dioxide, second nano silicon dioxide and third nano silicon dioxide, and the mass ratio is 1:1:1.
[0139] The volume concentration of ethanol in the ethanol aqueous solution is 65%.
[0140] The mass ratio of the nano silicon dioxide to the ethanol aqueous solution is 1:20.
[0141] The silane coupling agent is hexamethyldisilazane and γ-mercaptopropyltrimethoxysilane, and the mass ratio is 2:1.
[0142] The added amount of the silane coupling agent is 15% of the mass of the nano-silicon dioxide.
[0143] The mass ratio of the carbon fiber to acetone is 1:30.
[0144] The mass ratio of the modified nano-silica to toluene is 1:90.
[0145] The ultrasonic conditions are: power 150W, time 40min.
[0146] The mass ratio of the modified nano-silica to the activated carbon fiber is 1:3.
[0147] The added amount of the water reducing agent is 1.5% of the total mass of cement and fly ash.
[0148] In the raw materials for preparing the stress absorbing layer, the water-binder ratio is 0.25, the sand-binder ratio is 0.35, and the fiber mixing volume ratio is 2%.
[0149] The preparation method of the stress absorption layer comprises the following steps:
[0150] A1. Add the cementitious material and river sand into the mixer and stir at 120r / min for 4min;
[0151] A2. Mix water and water reducer, pour into a mixer, stir at 120r / min for 4 min, then stir at 250r / min for 4 min, sprinkle in fiber and stir at 250r / min for 8 min.
[0152] The raw materials for preparing the bonding layer include, by weight, 100 parts of a first matrix asphalt, 4 parts of rubber, 4 parts of a tackifying resin, and 0.5 parts of a first emulsifier.
[0153] The rubber is SBR.
[0154] The tackifying resin is petroleum resin.
[0155] The preparation method of the bonding layer comprises the following steps: heating the first matrix asphalt to 160°C, adding rubber, tackifying resin and the first emulsifier, stirring for 1.5 hours, heating to 175°C, shearing with a colloid mill at a speed of 3500 r / min for 1.5 hours, continuing to heat to 185°C, shearing with a colloid mill at a speed of 3500 r / min for 1.5 hours, stopping shearing, stirring and maturing for 45 minutes, and cooling to obtain the product.
[0156] The raw materials for preparing the asphalt concrete layer are modified asphalt, curing agent and mineral material.
[0157] The raw materials for preparing the modified asphalt are, by weight, 100 parts of second matrix asphalt, 5 parts of thermoplastic elastomer, 12 parts of epoxy resin, 0.5 parts of second matrix asphalt emulsifier, and 2 parts of epoxy resin emulsifier.
[0158] The thermoplastic elastomer is SBS.
[0159] The epoxy resin is bisphenol A type epoxy resin.
[0160] The preparation method of the modified asphalt comprises the following steps:
[0161] B1. Preparation of epoxy resin emulsion: epoxy resin, epoxy resin emulsifier and water are mixed, and sheared at a speed of 3500 r / min for 40 min to obtain epoxy resin emulsion;
[0162] B2. Preparation of modified second matrix asphalt: dissolving the second matrix asphalt emulsifier in 60° C. water to obtain a second matrix asphalt emulsifier solution; raising the temperature of the second matrix asphalt to 175° C., adding the second matrix asphalt emulsifier solution, shearing the mixture with a colloid mill at a speed of 3500 r / min for 30 min, adding a thermoplastic elastomer, continuing to shear the mixture with a colloid mill at a speed of 3500 r / min for 50 min, and cooling to obtain the modified second matrix asphalt;
[0163] B3. Mix the epoxy resin emulsion and the modified second matrix asphalt, and shear them at a speed of 400r / min for 8min.
[0164] The amount of water added in step B1 is consistent with the mass of epoxy resin.
[0165] The amount of water added in step B2 is 100 times the mass of the second matrix asphalt emulsifier.
[0166] The mineral materials include coarse aggregate, fine aggregate and filler. The specific proportions and properties refer to the article "Study on the Flexural Properties and Triaxial Static and Dynamic Characteristics of SBS Modified Asphalt Concrete for Anti-seepage Layer in Cold Regions" published by Ning Fengwei et al.
[0167] The mass ratio of the modified asphalt to the curing agent is 5:2.
[0168] The mass of the modified asphalt is 12% of the mass of the mineral material, and the gradation index is 0.43.
[0169] The preparation method of the asphalt concrete layer comprises the following steps: mixing the modified asphalt and the curing agent, shearing for 8 minutes at 155° C. and 1000 r / min, adding mineral material, and stirring for 30 minutes to obtain the asphalt concrete layer.
[0170] The preparation method of the multi-layer composite reinforced material comprises the following steps: simultaneously spreading a stress absorption layer, an adhesive layer, and an asphalt concrete layer, compacting the layer, and curing the layer at room temperature for 28 days to obtain the material.
[0171] The thickness of the stress absorbing layer is 8 mm.
[0172] The amount of the adhesive layer sprayed is 1.2 kg / m 2 .
[0173] The thickness of the asphalt concrete layer is 6 mm.
[0174] In some preferred embodiments, the stress absorbing layer and the asphalt concrete layer are heated to 185°C before spreading, and the bonding layer temperature is 165°C.
[0175] Example 2
[0176] The difference between this embodiment and embodiment 1 is that the thickness of the stress absorption layer is 10 mm.
[0177] The amount of the adhesive layer sprayed is 1.1 kg / m 2 .
[0178] The thickness of the asphalt concrete layer is 4 mm.
[0179] Comparative Example 1
[0180] The difference between this comparative example and Example 1 is that the fiber is PVA fiber.
[0181] Comparative Example 2
[0182] The difference between this comparative example and Example 1 is that the fibers are PVA fibers and carbon fibers, and the volume ratio is 2:1.
[0183] Comparative Example 3
[0184] The difference between this comparative example and Example 1 is that the nano-silicon dioxide is the first nano-silicon dioxide.
[0185] Comparative Example 4
[0186] The difference between this comparative example and Example 1 is that the raw materials for preparing the bonding layer include, by weight, 100 parts of a first matrix asphalt, 4 parts of a tackifying resin, and 0.5 parts of a first emulsifier.
[0187] Comparative Example 5
[0188] The difference between this comparative example and Example 1 is that the first matrix asphalt and the second matrix asphalt are consistent with each other, both of which are purchased from Maoming Branch of Sinopec Co., Ltd., No. 70 Road Petroleum Asphalt (1-4) (Grade A).
[0189] Comparative Example 6
[0190] The difference between this comparative example and Example 1 is that the raw materials for preparing the modified asphalt, by weight, are 100 parts of the second matrix asphalt, 5 parts of thermoplastic elastomer, 0.5 parts of the second matrix asphalt emulsifier, and 2 parts of epoxy resin emulsifier.
[0191] Comparative Example 7
[0192] The difference between this comparative example and Example 1 is that the raw materials for preparing the modified asphalt, by weight, are 100 parts of second matrix asphalt, 5 parts of EVA emulsion, 12 parts of epoxy resin, 0.5 parts of second matrix asphalt emulsifier, and 2 parts of epoxy resin emulsifier.
[0193] The EVA emulsion has a solid content of 53%-57% and a viscosity of 3500-4500 mP·a at 25° C. It is purchased from Dalian Chemical Industry Co., Ltd. in Taiwan, China, and is DA-102H.
[0194] Performance Testing
[0195] Referring to the method in patent CN 1083603277A, the Marshall method was used to test the high temperature rutting resistance (65°C dynamic stability) and low temperature crack resistance (bending failure strain, bending tensile strength, strain energy) of the multilayer composite reinforcement material. The higher the dynamic stability, the stronger the ability of the mixture to resist high temperature deformation; the greater the failure strain and strain energy, the better the low temperature crack resistance of the mixture. The results are shown in Table 1.
[0196] Table 1 Measurement results
[0197]
[0198] According to statistics, the multilayer composite reinforced materials prepared by Examples 1 to 2 of the present invention have strong high-temperature rutting resistance and low-temperature cracking resistance. Comparative Example 1 has only PVA fiber, Comparative Example 2 does not modify the carbon fiber, Comparative Example 3 has only the first nano-silica, Comparative Example 4 does not add SBR rubber to the bonding layer, Comparative Example 5 has the same first matrix asphalt as the second matrix asphalt, Comparative Example 6 does not add epoxy resin to the modified asphalt, and Comparative Example 7 uses EVA emulsion instead of thermoplastic elastomer SBS. The prepared multilayer composite reinforced material has poor high-temperature rutting resistance and low-temperature cracking resistance. Therefore, the multilayer composite reinforced material prepared by the raw materials and methods described in this application has excellent stress absorption, dispersion and bonding effects, can effectively alleviate the stress concentration caused by roadbed deformation, reduce the generation of reflective cracks, and significantly improve the overall stability and crack resistance of the road structure.
[0199] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A multi-layer composite reinforced material, characterized in that: From bottom to top, there are stress absorption layer, bonding layer and asphalt concrete layer; the raw materials for preparing the stress absorption layer include gelling material, river sand, fiber, water reducing agent and water; the fiber includes PVA fiber and modified carbon fiber; the diameter of the PVA fiber is 38-40 μm, the length is 12-13 μm, the tensile strength is 1550-1650 MPa, and the elongation at break is 6%-7%; the preparation method of the modified carbon fiber includes the following steps: S1. Modification of nano-silica: After nano-silica is dispersed evenly in an ethanol aqueous solution, a silane coupling agent is added, and the mixture is stirred at 60-70° C. for 4-6 hours, filtered, washed with deionized water for 2-3 times, filtered under reduced pressure, and dried in vacuum to obtain modified nano-silica; S2. Surface treatment and activation of carbon fiber: put the carbon fiber into a beaker containing acetone, use an ultrasonic cleaner to clean it 2-3 times, each time for 20-30 minutes, dry it, use oxygen plasma to treat the surface of the carbon fiber at a power of 45-55W, and the treatment time is 3-5 minutes to obtain activated carbon fiber; S3. Ultrasonic dispersion of modified nano-silica in toluene, immersion in activated carbon fiber, reaction at 80-100° C. for 3-5 hours, filtration, washing with ethanol for 3-5 times, and vacuum drying at 100° C. to obtain modified carbon fiber.
2. The multilayer composite reinforced material according to claim 1, characterized in that: The nano silicon dioxide comprises a first nano silicon dioxide, a second nano silicon dioxide and a third nano silicon dioxide.
3. The multilayer composite reinforced material according to claim 2, characterized in that: The mass ratio of the first nano-silicon dioxide, the second nano-silicon dioxide, and the third nano-silicon dioxide is (0.5-2):(0.5-2):
1.
4. The multilayer composite reinforced material according to claim 1, characterized in that: The carbon fiber has a diameter of 6 to 8 μm and a density of 1.70 to 1.80 g / cm 3 , elongation ≥1.5%, tensile strength ≥3GPa.
5. The multi-layer composite reinforced material according to claim 1, characterized in that: The raw materials for preparing the bonding layer include, by weight, 95-100 parts of a first matrix asphalt, 2-5 parts of rubber, 1-5 parts of a tackifying resin, and 0.5-1 parts of a first emulsifier.
6. The multilayer composite reinforced material according to claim 5, characterized in that: The softening point of the first matrix asphalt is 45-50°C, the needle penetration at 25°C is 80-85 (0.1 mm), the elongation at 10°C is 65-70 cm, and the dynamic viscosity at 60°C is 165-180 Pa·s.
7. The multi-layer composite reinforced material according to claim 5, characterized in that: The rubber comprises SBR; the styrene content of the SBR is 22%-25%, the elongation at break is ≥34%, and the volatility is 0.6%.
8. The multi-layer composite reinforced material according to claim 1, characterized in that: The raw materials for preparing the modified asphalt include, by weight, 95-105 parts of second matrix asphalt, 3-8 parts of thermoplastic elastomer, 8-15 parts of epoxy resin, 0.5-1 part of second matrix asphalt emulsifier, and 1-2.5 parts of epoxy resin emulsifier.
9. A method for preparing a multilayer composite reinforced material according to any one of claims 1 to 8, characterized in that: The steps are: simultaneously spreading the stress absorption layer, bonding layer and asphalt concrete layer, compacting and curing at room temperature for 28 days.
10. Use of the multilayer composite reinforcement material according to any one of claims 1 to 8 in preventing and controlling reflective cracks in widened roadbed.
Citation Information
Patent Citations
Preparation method of high-viscosity flexible normal-temperature construction stress absorbing layer mixture
CN110467389A
Anti-reflection crack pavement structure based on flexible transformation of rigid pavement
CN112779835A
Rigid stress absorbing layer for reflection crack prevention of composite pavement and preparation method of rigid stress absorbing layer
CN114772998A
Self-repairing rubber asphalt and preparation method thereof
CN118580688A
Alleviate road surface structure that reflective cracking produced
CN205975250U